Some Aspects of Breeding of Monal Pheasant (Lophophorus Impejanus) in Captivity - Suyal, B. D. (Indian Forester, 1991)
Monal pheasant at Sarahan pheasantry took quite long time (28 to 35 days) to lay her full clutch. The clutch was double (10 to 11 eggs), the size reported earlier. The fact that it lays on every alternate day was also disproved. A range of incubation period (26 to 29 days) rather than a fixed incubation period (26 to 29 days) was observed. Maximum success (73.33%) in terms of hatching was achieved at the end of 28 days. An ambient temperature zone of 15 to 200Â°C favoured laying of eggs. The fluctuations in ambient temperature shortened the incubation period.